Embodying the nation and the political contention: naturalised athletes changing (sportive) nationalism at the Beijing 2022 Olympics - Veronica Strina; Francesca Vomeri (SHARE Press, 2023)
During the 2022 Winter Games, China has lined its team up with an unprecedented number of athletes born and raised abroad. The two American-born sportswomen of Chinese descent, Gu Ailing and Zhu Yi, have been in the news spotlight for renouncing their US citizenship to compete under the Chinese flag, thus being caught in the middle of the Sino-US tensions. The article has a twofold purpose: on the one hand, it explores to what extent the US-China rivalry makes athletes pawns in the hands of states that struggle for supremacy; on the other hand, it seeks to show how the emergence of the phenomenon of athletes' naturalisation may contribute to the creation of a "multicultural nationalism" while leading to a surge of "negative" sportive nationalism, which assumes that the national interest comes at another nation's expense. The naturalisation of talents is no longer uncommon. Still, the way in which it is increasingly used in the context of the Games to feed the rivalry between states and shape the meaning of national identity is under-explored and therefore worth investigating.